Clinical and research priorities for combined modality therapy in stage III NSCLC. (April 2016) - Lin, Angela; Bezjak, Andrea
Stage III NSCLC comprises of a heterogeneous group of patients with regard to stage, extent of disease and prognosis. Disease presentation can often be complex in clinical practice, and the challenges are not well-defined in clinical trials or practice guidelines. In order to improve the therapeutic ratio of treatment, one needs to either increase the benefit of treatment or reduce toxicities, or both. Priorities in radiation therapy include dose escalation, imaging advances, improved target delineation, reduced planning target volume margin, intensity-modulated radiotherapy, image-guided radiotherapy, motion management and the use of cytoprotectants. Priorities in systemic therapy include the incorporation of molecularly targeted and immune-modulatory agents.